2004
DOI: 10.1177/175899830400900101
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Joint Stiffness in the Hand: A Preliminary Investigation of the Reliability and Validity of Torque Angle Curves

Abstract: The principal aim of this study was to examine aspects of the reliability and validity of the Torque Angle Curve (TAC) technique as a measure of joint stiffness. Specifically, inter-rater and intra-rater reliability were examined as well as the percent agreement of therapist evaluation of joint 'end feel' (i.e. springy or non-springy). Convergent validity of the TAC technique was studied by assessing the extent of agreement between TAC scores and therapist ratings of end feel. Thirty-eight joints were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…A more detailed reflection of the design diversity and results of the previous explorations is given in Additional file 9. Most of the intra-rater and inter-rater ICCs obtained in the current study were above 0.8, which indicates reliability [38] comparable with the previously reported values [6,10,11,17-20,25,27,29,33,37]. Most of the SEMs obtained in the current study are also in comparison with the corresponding estimates reported by the earlier researchers [9,29,33,37].…”
Section: Discussionsupporting
confidence: 91%
“…A more detailed reflection of the design diversity and results of the previous explorations is given in Additional file 9. Most of the intra-rater and inter-rater ICCs obtained in the current study were above 0.8, which indicates reliability [38] comparable with the previously reported values [6,10,11,17-20,25,27,29,33,37]. Most of the SEMs obtained in the current study are also in comparison with the corresponding estimates reported by the earlier researchers [9,29,33,37].…”
Section: Discussionsupporting
confidence: 91%
“…Previous research (Glasgow et al, 2003) indicated that 6-12 hr/day of splint use is better than <6 hr; however, limited evidence is available examining splint use beyond 12 hr. Some observable differences between groups existed at baseline, but overall the combined sample appeared to be representative of the wider population of handinjured patients undergoing PIP joint extension splinting (i.e., mostly men, little finger most commonly affected, average time since injury 10-11 wk; Glasgow et al, 2003;Glasgow, James, O'Sullivan, & Tooth, 2004;Prosser, 1996).…”
Section: Discussionmentioning
confidence: 97%